Identifying learning styles for effective learning and development in manufacturing industries using learning style questionnaire - Sadar Adi Pratomo, Dian; Welly, John (The Indonesian Journal of Business Administration, 2018)
Abstract—A start up training provider company has been running for one year and planning to incorporate experiential learning approach to improve its product so their client (learners) will have better learning outcome. Company needs to understand how experiential learning can deliver an optimal outcome to be gained by the learners (clients). Field research hence took place among manufacture workers at Cikarang Plant as one of Company’s clientele in December 2017. Research is designated to identify learners’ current learning styles and how they can gain benefit from experiential learning program. Analysis is using Learning Styles Questionnaire (LSQ) test by Honey & Mumford.  Test is performed among 30 employees with age ranging from 18 to 53 years old having high school to undergraduates as their last education and have working experience between 0 to 35 years. Conclusion is that 60% of their learning style is Activist-pragmatist. This style preference is caused by their age background and cognitive quotient accumulated throughout their life experience. There are two experiential learning solutions offered to enable an effective improvement of their learning styles. Those are audio-visual and on-line simulation game to be implemented by Company’s facilitators and adapted into identified learning styles.  Keywords: Learning Styles Questionnaire (LSQ), Experiential Learning, employee development, training program